Medical missions of the African Hungarian Union: The XIXth Special Surgical Doctors Mission to Malawi - Juhász, Péter Gergő; Loibl , Csaba; Szeremley, Csaba (Journal of Central and Eastern European African Studies, 2024)
This article discusses the charitable medical activities of the African Hungarian Union (AHU) – a Hungarian not-for-profit organization – in Africa and highlights one of the Ear-Nose-Throat (ENT) missions to Malawi. This paper also reviews food security issues in correlation with health and features the mission’s anaesthetic procedures in details. As an aim, it also tries to draw attention to the positive effects of such medical operations. AHU was established in 2006. Since 2009 the organisation has coordinated XXIV doctors’ missions to different African countries, including the Democratic Republic of Congo (DRC), Mali, Madagascar, Guinea, Uganda and Malawi. These missions were sponsored mainly by AHU and its individual sponsors and companies, as well as the participating doctors, who sometimes devoted not only their precious time but fundraised money to contribute to the budget. The XIX mission was one of the seven special surgical missions. Out of all the recipient countries—due to mainly logistical reasons from AHU’s side—only Malawi ended up in the fortunate situation to host surgical missions. This Medical Mission focused on Ear-Nose-Throat (ENT) surgeries, and general health care. The four Hungarian doctors, together with the local medical staff, performed 35 ENT operations in two operating theatres in two weeks. No postoperative Intensive Care Unit (ICU) admission was needed among the patients. Neither surgical nor anaesthesiologic complications occurred during the perioperative period, resulting in an overall very successful medical mission.